A PRISMA Systematic Review of Sexual Dysfunction and Probiotics with Pathophysiological Mechanisms - Su-Jin Yang; Trang Thi Minh Nguyen; Xiangji Jin; Qiwen Zheng; Se-Jig Park; Gyeong-Seon Yi; Tae-Hoo Yi (Biology)
Sexual dysfunction, influenced by hormonal imbalances, psychological factors, and chronic diseases, affects a significant portion of the population. Probiotics, known for their beneficial effects on gut microbiota, have emerged as potential therapeutic agents for improving sexual health. This systematic review evaluates the impact of probiotics on sexual function, hormonal regulation, and reproductive outcomes. A comprehensive search identified 3308 studies, with 12 meeting the inclusion criteria—comprising 10 randomized controlled trials (RCTs) and 2 in vivo and in vitro studies. Probiotic interventions were shown to significantly improve sexual function, particularly in women undergoing antidepressant therapy (p < 0.05). Significant improvements in Female Sexual Function Index (FSFI) scores were observed, with combined treatments such as Lactofem with Letrozole and Lactofem with selective serotonin reuptake inhibitors (SSRIs) demonstrating a 10% biochemical and clinical pregnancy rate compared to 0% in the control group (p = 0.05). Probiotic use was also associated with a 66% reduction in menopausal symptoms, increased sperm motility (36.08%), viability (46.79%), and morphology (36.47%). Probiotics also contributed to favorable hormonal changes, including a reduced luteinizing hormone (LH) to follicle-stimulating hormone (FSH) ratio (from 3.0 to 2.5, p < 0.05) and increased testosterone levels. Regarding reproductive outcomes, probiotic use was associated with higher pregnancy rates in women undergoing fertility treatments and improvements in sperm motility, viability, and morphology in men. This review highlights the promising role of probiotics in addressing sexual dysfunction and reproductive health, suggesting their potential as adjunctive treatments for conditions such as depression and infertility. Further research is needed to better understand the underlying mechanisms of these beneficial effects.